THE TURN OF THE SCREW & MORE GHOST STORIES - James, Henry, 1843-1916 (New York : UNION SQUARE KIDS, 2024)
The Turn of the Screw,' one of the most famous ghost stories of all time, a governess becomes obsessed with the belief that malevolent forces are stalking the children in her care. It is accompanied here by several more of the very best of Henry James's short stories, all exploring ghosts and the uncanny.
First published in 1898.
Keywords: Children's stories; Governesses -- Juvenile fiction; Orphans -- Care -- Juvenile fiction; Good and evil -- Juvenile fiction; London (England) -- History -- 1950; Great Britain -- History -- Victoria, 1837-1901; Ghost stories